Band gap engineering on CdS quantum dots through dual doping of Zn2+ and of Ni2+ ions. Issue 6 (July 2021) - Sakthivel, P.; Devadoss, I.; Krishnamoorthy, A.
Abstract: The CdS Quantum dots (QDs) have been synthesized without using any capping agent via a co-precipitation chemical route. The structural and optical investigations of the Ni 2+ -doped Cd0.9 Zn0.1 S QDs have been made. XRD patterns revealed that the synthesized QDs exhibit cubic structure and the particle size was measured ∼ 2 nm. EDX spectra showed that the existence of cadmium, zinc, sulphide, and nickel in the synthesized samples. FTIR spectra verified the vibrational peaks related to available molecules of elements in the samples. The absorbance rate of Ni 2+ -doped Cd0.9 Zn0.1 S QDs doped was more than Cd0.9 Zn0.1 S QDs in the visible region. The introduction of Ni 2+ ions into CdZnS QDs improved the optical transmittance in the visible spectrum and the band gap was blue-shifted for Ni = 6 at.% composition. The quantum confinement effect played an effective role in the band gap tailoring of CdS QDs via particle size tuning mechanism.